HPV Infection of the Head and Neck Region and Its Stem Cells. (November 2015) - Pullos, A.N.; Castilho, R.M.; Squarize, C.H.
The human papillomavirus (HPV) is an etiologic agent associated with the development of head and neck squamous carcinoma (HNSCC)—in particular, oropharyngeal squamous cell carcinoma. The HPV-positive HNSCC is characterized by genetic alterations, clinical progression, and therapeutic response, which are distinct from HPV-negative head and neck cancers, suggesting that virus-associated tumors constitute a unique entity among head and neck cancers. Malignant stem cells, or cancer stem cells, are a subpopulation of tumor cells that self-renew, initiate new tumors upon transplantation, and are resistant to therapy, and their discovery has revealed novel effects of oncovirus infection in cancer. In this review, we provide a virus-centric view and novel insights into HPV-positive head and neck pathogenesis. We discuss the influence of cancer stem cells, HPV oncoproteins, altered molecular pathways, and mutations in cancer initiation and cancer progression. We compiled a catalogue of the mutations associated with HPV-positive HNSCC, which may be a useful resource for genomic-based studies aiming to develop personalized therapies. We also explain recent changes in mass vaccination campaigns against HPV and the potential long-term impact of vaccinations on the prevention and treatment of HPV-positive head and neck cancers.